Hubungan Antara Motivasi dan Minat dengan Pemahaman Teknik Passing - Irawan Nugraha, Ahmad; Julianur; Tria Raharja, Andri (Jurnal Muara Olahraga, 2025)
Passing skills in football are basic talents that set good players apart, but there isn't much research on the psychological variables that affect skill acquisition in Indonesian schools. In May 2025, this correlational study looked at the connections between motivation, interest, and understanding of passing tactics among 31 football extracurricular students at SMAN 2 Samboja. It used Self-Determination Theory. We used the Sport Motivation Scale-II (α=0.847), the Individual Interest Scale (α=0.823), and the Understanding of Passing Techniques Scale (α=0.891) to gather data. Then, we used SPSS 26.0 to analyze the data using Pearson correlation and multiple regression. The results showed that the participants had a lot of motivation (M=5.42, SD=0.89), a lot of interest (M=4.18, SD=0.72), and a solid grasp of passing (M=3.85, SD=0.65). There were strong positive links between motivation and passing comprehension (r=0.672, p<0.001) and between curiosity and passing understanding (r=0.584, p<0.001). Motivation and interest together accounted for 52.3% of the variation in passing understanding (R²=0.523, p<0.001). Motivation was a better predictor (β=0.451) than interest (β=0.312). The results support the use of Self-Determination Theory in Indonesian sports education and suggest that encouraging independent motivation and situational interest might help students improve their technical skills in football extracurricular programs